Akibat Hukum Penggunaan Potret Idol Dalam Bentuk FanArt Pada Sampul Novel - Lefumonay, Imelda; Berlianty, Teng; Balik, Agustina (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2024)
Reading activities in today's digital era are increasingly accessible thanks to the abundance of information and communication. Access to a wide range of reading materials can now be done anywhere and anytime. One of the trends that has emerged in the publishing of fiction novels in Indonesia is the use of K-pop idol themes on book covers, especially those that have been registered with ISBNs. The covers of these novels often feature portraits of idols produced through fanart, tracing or other digital methods. For example, a novel called Hidden 2.O by Asabell Audida features the faces of EXO's Chanyeol and BTS's Jungkook drawn with vector techniques. However, this act of commercialization has the potential to violate the economic rights stipulated in Article 12 Paragraphs (1) and (2) of the UUHC, both for the idol concerned and the agency that oversees it. The research method used is juridical-normative with the approach used in this study being a conceptual approach and a statute approach. To answer the existing problems, the author collects legal materials through literature study and analysis with qualitative analysis methods. The results of the research regarding the use of images of Chanyeol from EXO and Jungkook from BTS as the cover of a novel by Asabell Audida without obtaining permission show that there is an unlawful act, which according to Article 9 Paragraph (2) of the UUHC the use of portraits for commercial purposes without the consent of the creator or copyright holder is a violation of the law. Therefore, fan artists who sell their works without permission can be considered to have committed an illegal act. And the legal consequences can be for the writer and also the legal consequences for the sale of the novel can be up to the revocation of the sales license.